Study of thermal deformation for selective laser melting in additive manufacturing - Ho, Brandon Jia Jun (Nanyang Technological University, 2023)
Selective Laser Melting (SLM) is a popular method of carrying out metal additive manufacturing. It involves building layers upon layers of melted feedstock using a high intensity laser to fuse a powder bed consisting of metal powder. Through this process, complex parts can be built with varying geometric designs. However, SLM is not without its limitations. Printing process parameters greatly affect the resulting physical properties and geometries of the part. Commonly, in-situ thermal gradients will result in the accumulation of residual stresses during the SLM process. The combined effect of residual stress and thermal contraction during the solidification of melted feedstock results in a final part deformation. This project aims to investigate the effects of varying two process parameters – scanning strategy and support structure design – on the final part deformation. An L16 Taguchi array was used to vary top tooth support length and scanning pattern. For each factor, 4 levels were tested in a total of 16 runs. The final part surface was scanned using a non-contact profiler, the Keyence Laser Microscope. Thereafter, the maximum deformation was calculated. Finally, a smaller is better signal-to-noise ratio was used to identify the most impactful print settings and the results were explained using a thermal model of the printing process via COMSOL Multiphysics. From the SLM print, the top tooth length of 1mm and a 45 scanning strategy yielded a part with the least deformation. Aside from deformation, it was also observed that surface texture varied from print to print, as a side effect of changing print parameters. As such, a preliminary analysis was also done to investigate this phenomenon.